2012
DOI: 10.1371/journal.pone.0043848
|View full text |Cite
|
Sign up to set email alerts
|

HPLC–MS/MS Analysis of a Traditional Chinese Medical Formulation of Bu-Yang-Huan-Wu-Tang and Its Pharmacokinetics after Oral Administration to Rats

Abstract: Bu-yang-huan-wu-tang (BYHWT) is one of the most popular formulated traditional Chinese medicine prescriptions, and is widely for prevention of ischemic cardio-cerebral vascular diseases and stroke-induced disability. A specific high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) has been developed and validated for simultaneous quantification of the nine main bioactive components, i.e., astragaloside I, astragaloside II, astragaloside IV, formononetin, ononin, calycosin, calycosin-7-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 35 publications
2
41
0
1
Order By: Relevance
“…As every formulation is composed with multiple herbs, herbs and ingredients may affect and interact with each other because of different physical and chemical characteristics . A previous in vitro study indicated that berberine content (8.15 ± 0.39 mg/g) in herbal formulation of Huang‐Lian‐Jiee‐Dwu‐Tang appeared to be less in the single herb Coptidis Radix (53.63 + 2.45 mg/g) but higher in Phellodendri Cortex (3.02 + 0.22 mg/g) when extracted with water.…”
Section: Discussionmentioning
confidence: 99%
“…As every formulation is composed with multiple herbs, herbs and ingredients may affect and interact with each other because of different physical and chemical characteristics . A previous in vitro study indicated that berberine content (8.15 ± 0.39 mg/g) in herbal formulation of Huang‐Lian‐Jiee‐Dwu‐Tang appeared to be less in the single herb Coptidis Radix (53.63 + 2.45 mg/g) but higher in Phellodendri Cortex (3.02 + 0.22 mg/g) when extracted with water.…”
Section: Discussionmentioning
confidence: 99%
“…There are nine main bioactive components, i.e., astragaloside I, astragaloside II, astragaloside IV, formononetin, ononin, calycosin, calycosin-7-O-β-d-glucoside, ligustilide and paeoniflorin in Buyanghuanwu Tang extract (56). This traditional herbal formulation has been widely used in Chinese clinical practice for treatment and prevention of ischemic cardio-cerebral vascular diseases and strokeinduced disability for thousands of years.…”
Section: Chinese Herbal Medicinementioning
confidence: 99%
“…At 1 h after the last administration, blood was obtained via cardiac puncture from each group, and defined as the BYHWD-containing serum (BYHWD-CS) and vehicle containing serum (vehicle-CS) samples, respectively. All samples were heated at 56˚C for 30 min to be inactivated, then filtered and kept at -20˚C until further use (16).…”
Section: Preparation Of Byhwd-cs Byhwd Was Obtained Frommentioning
confidence: 99%
“…Whether BYHWD directly influences the astrocytic GLT-1/GS levels (through neurons or other types of cells) is not fully understood, and the potential mechanisms remain unknown. Nine bioactive components (including astragaloside I, astragaloside II, astragaloside IV, formononetin, ononin, calycosin, calycosin-7-O-β-d-glucoside, ligustilide and paeoniflorin) have been identified in the plasma subsequent to BYHWD treatment (16). Therefore, it is difficult to use only specific components of the formula to investigate the protective role of BYHWD.…”
Section: Introductionmentioning
confidence: 99%